1998
DOI: 10.1111/j.1530-0277.1998.tb03669.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Muscle Levels of α‐Tocopherol, Ascorbic Acid, and Retinol Are Normal in Chronic Alcoholic Myopathy

Abstract: Some authors have suggested a possible loss of antioxidant factors in alcoholic skeletal myopathy. To assess the relationship between ethanol consumption and serum and muscle levels of alpha-tocopherol, ascorbic acid, and retinol in chronic alcoholics with and without skeletal myopathy, a prospective cross-sectional study was performed in the Alcohol Unit of a 1000-bed university hospital. Twenty-five chronic male alcoholic patients (10 with skeletal myopathy) and 15 male controls of similar age were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 21 publications
2
11
1
1
Order By: Relevance
“…In accordance with some earlier studies, significantly lower concentrations of a-tocopherol and gtocopherol were observed in alcohol consumers (Addolorato, 1998;Bjorneboe et al, 1988;Mills et al, 1983). However, in other studies unchanged (Bode et al, 1988;Fernandez-Sola et al, 1998;Rissanen et al, 1987), and even increased (Simonetti et al, 1995) plasma concentrations of tocopherol were found in alcohol imbibers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with some earlier studies, significantly lower concentrations of a-tocopherol and gtocopherol were observed in alcohol consumers (Addolorato, 1998;Bjorneboe et al, 1988;Mills et al, 1983). However, in other studies unchanged (Bode et al, 1988;Fernandez-Sola et al, 1998;Rissanen et al, 1987), and even increased (Simonetti et al, 1995) plasma concentrations of tocopherol were found in alcohol imbibers.…”
Section: Discussionsupporting
confidence: 87%
“…In the latter case the results are also likely to depend on the selection of criteria such as clinical or laboratory signs of overt malnutrition or reduced blood content of micronutrients. Finally, the ethnic background and differences in the type of dietary habits may, at least partially, play a role in the discordant results on the nutrient intake and=or nutritional status of alcohol consumers in different countries (Addolorato et al, 2000;Fernandez-Sola et al, 1998;Gloria et al, 1997;Mezey, 1991;Rissanen et al, 1987;Sarin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a daily treatment regimen of alpha-tocopherol supplementation (30 mg/kg per day for 5 days), the acute dose of ethanol still reduces skeletal muscle protein synthesis (33). More recently, studies have shown that in Spanish alcohol misusers with myopathy, both serum and muscle levels of alpha-tocopherol did not influence the presence of skeletal muscle myopathy in chronic alcoholic patients (34). These observations contrast with a UK study, which showed reduced serum alpha-tocopherol and selenium in myopathic alcoholics, which may reflect geographical differences in antioxidant intake (8,34).…”
Section: Protective Effects Of Alpha-tocopherol and Seleniummentioning
confidence: 99%
“…Патогенез ХАМ до конца не изучен. Установлено, что развитие ХАМ не зависит от наличия алкогольной полинейропатии, алко-гольного поражения печени, полидефицитарных состоя-ний, гормональных нарушений и напрямую не связано с процессами апоптоза [2,7]. В то же время ХАМ может со-четаться с другими признаками алкогольной болезни [8,9].…”
unclassified